Application and Exploration of VR and AI Technology in College English Teaching - Zhaodan Yang (Advances in Multimedia)
In order to improve the effect of college English teaching, this article applies VR and AI technology to college English teaching. According to the pixel structure of English teaching image and its array drive design, this article proposes a semiactive address-driven pixel structure. Moreover, this article controls the scanning rate by adjusting the period of the clock signal CLK generated by the computer or FPGA, which determines the speed of image transmission. In addition, in order to determine the output DC value of the cascode structure, the negative feedback loop is biased, and an intelligent teaching system is constructed. According to the teaching evaluation research, it can be seen that the college English teaching method based on VR technology and AI technology proposed in this article can effectively improve the teaching effect of college English.